Perovskite / silicon laminated solar cell with selective passivation contact structure and preparation method thereof
By forming a selective passivation layer in the bottom area of the micro pyramid structure of the perovskite/silicon stacked solar cells, the energy loss problem caused by the interface non-radiative recombination is solved, efficient carrier transmission is achieved, and the photoelectric conversion efficiency of the solar cells is improved.
Patent Information
- Application Number
- CN202411944803.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
AI Technical Summary
In perovskite/silicon stacked solar cells, the interface of the micro-pyramid structure results in low photogenerated carrier density and large specific surface area, resulting in energy loss of non-radiative recombination of the interface, and existing interface engineering methods will hinder carrier transmission.
Using a selective passivation contact structure, a selective passivation layer is formed by polymerizing in situ in the bottom of the hole transport layer pyramid structure, and a passivation state is formed only in the bottom area of the micro pyramid structure, inhibiting non-radiative recombination at the interface without affecting carrier transmission.
It effectively suppresses the non-radiative recombination of the interface, improves the photoelectric conversion efficiency and working stability of perovskite/silicon stacked solar cells, and the photoelectric conversion efficiency reaches 30.74%.
Smart Images

Figure CN119744071A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a perovskite / silicon stacked solar cell with a selective passivation contact structure and a preparation method thereof, belonging to the technical field of solar cells. Background Art
[0002] In recent years, as the photoelectric conversion efficiency of crystalline silicon solar cells has reached 27.3%, it is getting closer to the Auger recombination limit of 29.4%, and it is becoming increasingly difficult to further improve the energy conversion efficiency of single-crystal silicon solar cells. Wide-bandgap perovskite materials are suitable as top cells of stacked solar cells due to their adjustable bandgap and low-temperature preparation process. Perovskite materials have a special ABX3 crystal structure, where A is formamidine (FA + ), methylamine (MA + ) or cesium (Cs + ) and other inorganic cations; B is lead (Pb 2+ ), tin (Sn 2+ ) or other positive divalent metal ions; X is iodine (I – ), bromine (Br – ), chlorine (Cl – ) and other halogen ions. The photoelectric conversion efficiency of perovskite / silicon stacked solar cells based on perovskite light-absorbing materials has reached 34.6%, becoming a research hotspot in the current photovoltaic field. Due to the extremely high extinction coefficient of perovskite materials, about 90% of the photogenerated carriers are only generated within 100 nanometers of the light-receiving surface. However, on the surface of common commercial crystalline silicon cells, there are micro-pyramid structures produced by alkaline etching processes. Larger micro-pyramids may pierce the thin perovskite layer deposited non-conformally, thereby increasing the thickness requirements for the perovskite light-absorbing layer deposited by the solution method. The contradiction between the carrier generation position and the thickness of the perovskite layer causes the perovskite material in the groove area of the micro-pyramid structure to present a problem of low photogenerated carrier density and large specific surface area; therefore, in this area, the energy loss caused by interface non-radiative recombination accounts for a higher proportion. Existing interface engineering, etc., can inhibit the carrier recombination assisted by semiconductor surface defects and the non-radiative recombination of semiconductor interfaces by forming an insulating material layer at the interface or passivating interface defects, but it will also partially hinder the transmission of carriers at the interface. Taking into account the carrier diffusion within the perovskite material, at the interface of the micro-pyramid structure below the perovskite, the charge transfer surface density tends to increase as it approaches the tip of the micro-pyramid; therefore, using selective means to form a passivation state with a significant difference between the tip and the bottom of the micro-pyramid structure on the surface has become an effective strategy for preparing efficient and stable perovskite / silicon tandem solar cells. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a perovskite / silicon tandem solar cell with a selective passivation contact structure and a preparation method thereof. The strategy of selectively passivating the surface of the micro-pyramid structure in the present invention can inhibit the non-radiative recombination of the lower interface of the wide-bandgap perovskite film on the micro-texture silicon, stabilize the lower interface of the perovskite, and have no adverse effect on carrier transport, so as to improve the photoelectric conversion efficiency and working stability of the perovskite / silicon tandem solar cell device.
[0004] To achieve the above objectives, the technical solution of the present invention is as follows.
[0005] A perovskite / silicon stacked solar cell with a selective passivation contact structure comprises a silicon solar cell and a wide bandgap perovskite solar cell arranged from bottom to top, wherein the upper surface of the silicon solar cell is a pyramid structure, and the wide bandgap perovskite solar cell is a trans structure, and the wide bandgap perovskite solar cell comprises a hole transport layer arranged conformally with the pyramid structure, a selective passivation layer formed of a non-conformal insulating high molecular polymer is arranged in the pyramid bottom region of the hole transport layer, and a perovskite light absorbing layer is arranged on the surface of the selective passivation layer and the exposed surface of the hole transport layer.
[0006] Preferably, the insulating high molecular polymer includes polystyrene, polyphenyl methacrylate or polyglycerol trihydroxypropyl ether triacrylate.
[0007] Preferably, the pyramid structure on the upper surface of the silicon solar cell is a plurality of regular tetrahedrons with base lengths of 100 to 2000 nanometers, and the height of each regular tetrahedron is 0.6 to 0.8 times the length of its base; the insulating high molecular polymer in the selective passivation layer covers 5% to 60% of the surface area of the hole transport layer; preferably, the insulating high molecular polymer in the selective passivation layer covers 10% to 30% of the surface area of the hole transport layer.
[0008] Preferably, the stacked solar cell includes a heterojunction silicon cell, a carrier recombination layer, a hole transport layer, a selective passivation layer, a perovskite light absorption layer, an electron transport layer, a buffer layer, a transparent electrode and a metal electrode, which are arranged in sequence from bottom to top.
[0009] A method for preparing a perovskite / silicon tandem solar cell with a selective passivation contact structure according to the present invention, the method steps comprising:
[0010] (1) preparing a silicon solar cell with a pyramid structure on the upper surface;
[0011] (2) conformally growing a hole transport layer on the surface of a silicon solar cell;
[0012] (3) in situ polymerizing an insulating high molecular polymer at the bottom of the pyramid structure of the hole transport layer to obtain a selective passivation layer;
[0013] (4) Growing a perovskite light absorbing layer on the surface of the selective passivation layer and the exposed surface of the hole transport layer.
[0014] Preferably, in step (3), when the insulating high molecular polymer is in situ polymerized, the polymer monomer and the photoinitiator are dissolved in an organic solvent to obtain a polymer monomer solution; the polymer monomer solution is spin-coated on the bottom of the pyramid structure of the hole transport layer, first at a high speed and then at a low speed, so that the solution is partially volatilized, and then photo-initiated polymerization is performed, and annealing is performed to obtain a selective passivation layer.
[0015] Preferably, the polymer monomer includes styrene, phenyl methacrylate or trihydroxypropyl ether triacrylate.
[0016] Preferably, the photoinitiator is benzoin ethyl ether; and the organic solvent is tetrahydrofuran.
[0017] Preferably, the polymer monomer accounts for 0.10% to 5.00% of the mass of the polymer monomer solution, the photoinitiator accounts for 0.02% to 0.10% of the mass of the polymer monomer solution, and the organic solvent accounts for 94.90% to 99.88% of the mass of the polymer monomer solution.
[0018] Preferably, firstly, spin coating is performed at a high speed of 3500 to 4500 rpm for 5 to 10 seconds, then spin coating is performed at a low speed of 1000 to 2000 rpm for 5 to 20 seconds to partially volatilize the solution, the spin coating rate is kept constant, ultraviolet irradiation is performed for 15 to 20 seconds, and finally annealing is performed at 100 to 110° C. for 1 to 5 minutes.
[0019] Preferably, when the polymer monomer is styrene, it is prepolymerized by ultraviolet irradiation for 20 to 30 seconds before spin coating; when the polymer monomer is glycerol trihydroxypropyl ether triacrylate, after low-speed spin coating, it is heated at below 150° C. for 10 to 30 seconds to promote volatilization of the polymer monomer.
[0020] Beneficial Effects
[0021] The present invention utilizes a non-conformal selective passivation layer between the hole transport layer and the perovskite light absorbing layer to passivate the bottom region of the micro-pyramid structure of the lower interface of the perovskite, thereby inhibiting the interface non-radiative recombination while not affecting the carrier transport in other regions, thereby preparing a highly efficient perovskite / crystalline silicon tandem cell. Ultimately, the photoelectric conversion efficiency of the perovskite / silicon tandem solar cell based on the inverted perovskite half-cell reaches 30.74%.
[0022] The present invention uses a non-conformal method to form a network of discontinuous interface passivation areas with insulating high molecular polymers that only exist in the bottom area of the micro-pyramid structure, and does not cover the top area of the micro-pyramid with a higher charge transfer density, thereby suppressing interface non-radiative recombination without affecting the main charge transfer. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1-2 It is a schematic diagram of the surface of the stacked solar cell structure of the present invention.
[0024] Figure 3 This is a scanning electron microscope backscattered electron image of the selective passivation layer on the surface of the micro-pyramid structure in Example 1-3.
[0025] Figure 4 This is the conductivity distribution diagram of the micro-area on the surface of the micro-pyramid structure based on the selective passivation layer in Example 1.
[0026] Figure 5 This is a distribution diagram of the quasi-Fermi level splitting (QFLS) of the perovskite layer on the textured silicon surface of the selective passivation layer in Example 4.
[0027] Figure 6 This is a comparison diagram of the voltage-current density curves of the perovskite / silicon stacked device based on the selective passivation layer in Example 5 and the unregulated stacked device. DETAILED DESCRIPTION
[0028] The present invention will be further described in detail below in conjunction with specific embodiments.
[0029] like Figure 1-2 As shown, a perovskite / silicon stacked solar cell with a selective passivation contact structure includes a silicon solar cell and a wide-bandgap perovskite solar cell arranged from bottom to top, the upper surface of the silicon solar cell is a pyramid structure, the wide-bandgap perovskite solar cell is a trans structure, the wide-bandgap perovskite solar cell includes a hole transport layer arranged conformally with the pyramid structure, a selective passivation layer formed of a non-conformal insulating high molecular polymer is provided in the pyramid bottom region of the hole transport layer, and a perovskite light absorbing layer is provided on the surface of the selective passivation layer and the exposed surface of the hole transport layer.
[0030] In some embodiments, the insulating high molecular polymer includes polystyrene, polyphenyl methacrylate or polytrihydroxypropyl ether triacrylate.
[0031] In some embodiments, the pyramid structure on the upper surface of the silicon solar cell is a plurality of regular tetrahedrons with a base length of 100 to 2000 nanometers, and the height of each regular tetrahedron is 0.6 to 0.8 times the length of its base. The hole transport layer is conformally deposited on the surface of the silicon solar cell and is consistent with the surface morphology of the silicon solar cell. The structure of the selective passivation layer requires that the insulating polymer is only distributed near the bottom of the pyramid structure and covers 5% to 60% of the surface area of the hole transport layer. Preferably, the insulating polymer in the selective passivation layer covers 10% to 30% of the surface area of the hole transport layer.
[0032] In some embodiments, the stacked solar cell includes a heterojunction silicon cell, a carrier recombination layer, a hole transport layer, a selective passivation layer, a perovskite light absorption layer, an electron transport layer, a buffer layer, a transparent electrode and a metal electrode arranged in sequence from bottom to top.
[0033] A method for preparing a perovskite / silicon tandem solar cell with a selective passivation contact structure according to the present invention, the method steps comprising:
[0034] (1) preparing a silicon solar cell with a pyramid structure on the upper surface;
[0035] (2) conformally growing a hole transport layer on the surface of a silicon solar cell;
[0036] (3) in situ polymerizing an insulating high molecular polymer at the bottom of the pyramid structure of the hole transport layer to obtain a selective passivation layer;
[0037] (4) Growing a perovskite light absorbing layer on the surface of the selective passivation layer and the exposed surface of the hole transport layer.
[0038] (5) preparing an electron transport layer on the perovskite light absorbing layer;
[0039] (6) preparing a buffer layer on the electron transport layer;
[0040] (7) preparing a transparent electrode on the buffer layer;
[0041] (8) Prepare a metal electrode on the transparent electrode.
[0042] In some embodiments, in step (3), when the insulating high molecular polymer is polymerized in situ, the polymer monomer and the photoinitiator are dissolved in an organic solvent to obtain a polymer monomer solution; the polymer monomer solution is coated on the bottom of the pyramid structure of the hole transport layer, and after partial volatilization, photoinitiated polymerization is performed to obtain a selective passivation layer. Specifically, the non-conformal deposition method includes three characteristic steps: coating, partial volatilization, and photoinitiated polymerization. In the coating step, the polymer monomer and an appropriate amount of photopolymerization initiator are co-dissolved in a volatile solvent such as tetrahydrofuran to form a dilute solution; the dilute solution can be deposited on the surface having a micro-pyramid structure by liquid coating methods such as spin coating, scraping, and inkjet printing. In the partial volatilization step, the polymer monomer that has not yet been polymerized will partially volatilize at room temperature or under heating conditions not higher than 150°C; a small amount of polymer monomer attached to the tip of the micro-pyramid structure will leave, thereby enhancing the difference between the tip and the bottom of the micro-pyramid structure of this method. In the photo-initiated polymerization step, ultraviolet irradiation with a wavelength of 365 nm of appropriate intensity can activate the photoinitiator, causing the polymer monomers to polymerize according to the free radical polymerization pathway to form polymers that are insoluble or slightly soluble in the perovskite sol solution.
[0043] In some embodiments, the polymer monomer includes one or more of styrene, phenyl methacrylate, and tris(hydroxypropyl) ether triacrylate.
[0044] In some embodiments, the photoinitiator is benzoin ethyl ether; and the organic solvent is tetrahydrofuran.
[0045] In some embodiments, the polymer monomer accounts for 0.50% to 4.00% of the mass of the polymer monomer solution, the photoinitiator accounts for 0.04% to 0.05% of the mass of the polymer monomer solution, and the organic solvent accounts for 95.95% to 99.46% of the mass of the polymer monomer solution.
[0046] In some embodiments, the solution is firstly spun at a high speed of 3500-4500 rpm for 5-10 seconds, then spun at a low speed of 1000-2000 rpm for 5-20 seconds to partially evaporate the solution, the spin coating rate is kept constant, ultraviolet irradiation is performed for 15-20 seconds, and finally annealing is performed at 100-110°C for 1-5 minutes.
[0047] In some embodiments, when the polymer monomer is styrene, it is pre-polymerized by ultraviolet irradiation for 20 to 30 seconds before spin coating; when the polymer monomer is trihydroxypropyl ether triacrylate, after low-speed spin coating, it is heated at below 150° C. for 10 to 30 seconds to promote volatilization of the polymer monomer.
[0048] Example 1
[0049] (1) Preparation of heterojunction silicon cells: chemically polishing an n-type single crystal silicon wafer to remove impurities such as oil stains and metal particles on the surface of the silicon wafer; forming a phosphorus diffusion layer on the surface of the silicon wafer by diffusion; removing the phosphorus diffusion layer by an alkaline solution to form a micro-pyramid structure texture on the surface of the silicon wafer; depositing an amorphous silicon thin film layer on the front and back of the textured silicon wafer; depositing a conductive thin film layer (composite layer) on the front and back of the amorphous silicon thin film layer; and covering the conductive thin film layer on the back with a metal electrode;
[0050] (2) Preparation of hole transport layer: 1 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid and 1 mg of [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphoric acid were dissolved in 2 ml of ethanol, and the mixture was spin-coated at 3000 rpm for 30 seconds, followed by annealing at 100° C. for 10 minutes to form a self-assembled monolayer hole transport layer;
[0051] (3) Preparation of a selective passivation layer: 20.8 mg of phenyl methacrylate liquid, 0.4 mg of benzoin ethyl ether, and 872.2 mg of tetrahydrofuran were mixed; the obtained mixed solution was dripped onto the micro-fleece surface of the hole transport layer and spin-coated using a sizing machine: in the first step, the rotation speed was increased to 4000 rpm for 5 seconds; in the second step, the rotation speed was reduced to 1000 rpm for 5 to 20 seconds; in the third step, the sizing machine was kept at 1000 rpm and 0.1 W / cm2 of ultraviolet light with a wavelength of 365 nm was used to irradiate the solution in the spin coating for 15 seconds. Subsequently, the solution was annealed at 100°C for 1 minute to form a selective passivation layer.
[0052] The hole transport layer with a selective passivation layer was tested under an atomic force microscope: a conductive probe was selected and the test voltage was set to -1 volt to study the distribution of surface conductivity. The results are shown in Figure 2. Figure 4 As shown in the figure, it can be observed that low probe current areas appear between the micro-pyramid structures on the surface of the sample deposited with the selective passivation layer, indicating that there are insulating or low-conductivity materials in this area. In addition, as the spin coating time of the coater before UV irradiation is shortened, the evaporation of the polymer monomer in the evaporation step is reduced, and the low conductivity area on the sample surface is widened, and the surface area occupied is increased, but it does not occupy the top of the micro-pyramid structure.
[0053] Figure 3 This is a backscattered electron image of the polymer in the selective passivation layer under a scanning electron microscope. Since the larger the atomic number, the stronger the ability of its nucleus to reflect electrons, the backscattered electron image of the scanning electron microscope can show the difference in atomic number. The brighter area of the image indicates the area with a larger average atomic number. Since the main components of the above polymers are carbon, hydrogen, oxygen, etc., which are smaller than the silicon, indium, and tin on the surface of the micro-textured heterogeneous crystalline silicon solar cell, they appear as darker areas in the image.
[0054] Example 2
[0055] In this embodiment, steps (1)-(2) are the same as those in Example 1.
[0056] (3) 36.2 mg of styrene liquid, 0.4 mg of benzoin ethyl ether, and 854.4 mg of tetrahydrofuran were mixed; the obtained mixed solution was dripped onto the micro-fleece surface of the hole transport layer and the solution was spread; the solution was irradiated with ultraviolet light of 0.1 W / cm2 and 365 nm wavelength for 30 seconds to prepolymerize it; spin coating was performed using a coating machine at a speed of 4000 rpm for 5 seconds; the spin-coated crystalline silicon solar cell was placed on a hot stage at 100 degrees Celsius and heated for 5 seconds to partially volatilize the prepolymerized product; the heat-treated crystalline silicon solar cell was removed from the hot stage and irradiated with ultraviolet light of 0.1 W / cm2 and 365 nm wavelength for 15 seconds to completely polymerize it; the crystalline silicon solar cell with the polymer was annealed at 100 degrees Celsius for 1 minute to prepare a selective passivation layer.
[0057] The surface scanning electron microscope backscattered electron image results are similar to those in Example 1.
[0058] Example 3
[0059] In this embodiment, steps (1)-(2) are the same as those in Example 1.
[0060] (3) 5.32 mg of glycerol trihydroxypropyl ether triacrylate liquid, 0.4 mg of benzoin ethyl ether, and 885.5 mg of tetrahydrofuran are mixed; the obtained mixed solution is dripped onto a micro-textured heterogeneous crystalline silicon solar cell having a hole transport layer, and spin-coated using a coater at a speed of 4000 rpm for 5 seconds; the spin-coated micro-textured heterogeneous crystalline silicon solar cell is placed on a hot plate at 100 degrees Celsius, and heated for 30 seconds to partially volatilize the monomer; the heat-treated crystalline silicon solar cell is removed from the hot plate, and irradiated with 0.1 watts / square centimeter ultraviolet light at a wavelength of 365 nm for 15 seconds to completely polymerize it; the crystalline silicon solar cell with the polymer is annealed at 100 degrees Celsius for 1 minute to prepare a selective passivation layer.
[0061] The surface scanning electron microscope backscattered electron image results are similar to those in Example 1.
[0062] Example 4
[0063] In this embodiment, steps (1) to (3) are the same as those in Example 1.
[0064] (4) 6.7 mg of methylamine hydrochloride, 27.8 mg of lead chloride, 103.9 mg of cesium iodide, 146.8 mg of lead bromide, 275.1 mg of formamidine hydroiodide, and 737.6 mg of lead iodide were dissolved in a mixed solvent of 1000 μL of N,N-dimethylformamide (DMF) and 120 μL of N-methylpyrrolidone (NMP), and stirred at room temperature for 10 hours. The entire solution was then added to another reagent bottle containing 0.4 mg of L-α-phosphatidylcholine, 2.4 mg of p-4-trifluoromethylphenylethylamine hydroiodide, 10.0 mg of methylamine hydrochloride, and 14.0 mg of propylamine hydrochloride, and stirred at room temperature for 2 hours. The mixture was spin-coated on the exposed surfaces of the selective passivation layer and the hole transport layer for 45 seconds using a coater at a speed of 3000 rpm with the assistance of nitrogen blowing, and then annealed at 120°C for 45 minutes to prepare a perovskite light absorbing layer.
[0065] like Figure 5 As shown in the figure, the samples with and without the selective passivation layer between the hole transport layer and the perovskite light absorption layer were placed under 100 mW / cm2 of 400 nm wavelength excitation light, the exposure time was set to 100 ms, the excitation photons were collected, and the quasi-Fermi level splitting of the perovskite film was calculated. The results show that the quasi-Fermi level splitting of the perovskite film without the selective passivation layer on the underlying surface is 1.265 volts, while the quasi-Fermi level splitting of the perovskite film with the selective passivation layer on the underlying surface is 1.312 volts, indicating that the selective passivation layer on the underlying surface can effectively suppress the non-radiative recombination of carriers at the perovskite-hole transport layer interface in the open circuit state.
[0066] Example 5
[0067] In this embodiment, steps (1) to (5) are the same as those in Example 1.
[0068] (5) Preparation of electron transport layer: A 15 nm thick fullerene layer was prepared by vacuum thermal evaporation method;
[0069] (6) Preparation of buffer layer: A 10 nm thick tin oxide layer was prepared by atomic layer deposition;
[0070] (7) Preparation of transparent electrode: Preparation of ITO transparent electrode by magnetron sputtering method;
[0071] (8) Preparation of metal grid lines: Gold / silver electrodes are prepared by vacuum evaporation method.
[0072] like Figure 6 As shown in FIG. 1 , a perovskite / silicon tandem solar cell device including a selective passivation layer and a perovskite / silicon tandem solar cell device without a selective passivation layer is placed under a standard sunlight and a voltage-current density curve is scanned. Among them, the current density of the tandem solar cell including the selective passivation layer is 20.41 mA / cm 2, the open circuit voltage is 1.922V, the fill factor is 78.86%, and the photoelectric conversion efficiency is 30.94%. The current density of the perovskite / silicon stacked solar cell device without the selective passivation layer is 20.53mA / cm 2 , the open circuit voltage is 1.913V, the fill factor is 76.37%, and the photoelectric conversion efficiency is only 30.00%.
[0073] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A perovskite / silicon tandem solar cell with a selectively passivated contact structure, characterized in that: It includes a silicon solar cell and a wide-bandgap perovskite solar cell arranged from bottom to top, the upper surface of the silicon solar cell is a pyramid structure, the wide-bandgap perovskite solar cell is a trans structure, the wide-bandgap perovskite solar cell includes a hole transport layer arranged conformally with the pyramid structure, a selective passivation layer formed of a non-conformal insulating high molecular polymer is arranged in the pyramid bottom area of the hole transport layer, and a perovskite light absorption layer is arranged on the surface of the selective passivation layer and the exposed surface of the hole transport layer.
2. A perovskite / silicon tandem solar cell with a selective passivation contact structure as claimed in claim 1, characterized in that: The insulating high molecular polymer includes polystyrene, polyphenyl methacrylate or polyglycerol trihydroxypropyl ether triacrylate.
3. A perovskite / silicon tandem solar cell with a selective passivation contact structure as claimed in claim 1, characterized in that: The pyramid structure on the upper surface of the silicon solar cell is a plurality of regular tetrahedrons with base lengths of 100 to 2000 nanometers, and the height of each regular tetrahedron is 0.6 to 0.8 times the length of its base; the insulating high molecular polymer in the selective passivation layer covers 5% to 60% of the surface area of the hole transport layer.
4. A perovskite / silicon tandem solar cell with a selective passivation contact structure as claimed in claim 3, characterized in that: The insulating high molecular polymer in the selective passivation layer covers 10% to 30% of the surface area of the hole transport layer.
5. The perovskite / silicon tandem solar cell with a selective passivation contact structure according to claim 1, characterized in that: The stacked solar cell comprises a heterojunction silicon cell, a carrier recombination layer, a hole transport layer, a selective passivation layer, a perovskite light absorption layer, an electron transport layer, a buffer layer, a transparent electrode and a metal electrode which are arranged in sequence from bottom to top.
6. A method for preparing a perovskite / silicon tandem solar cell with a selective passivation contact structure according to any one of claims 1 to 5, characterized in that: The method steps include: (1) preparing a silicon solar cell with a pyramid structure on the upper surface; (2) conformally growing a hole transport layer on the surface of a silicon solar cell; (3) in situ polymerizing an insulating high molecular polymer at the bottom of the pyramid structure of the hole transport layer to obtain a selective passivation layer; (4) Growing a perovskite light absorbing layer on the surface of the selective passivation layer and the exposed surface of the hole transport layer.
7. The method for preparing a perovskite / silicon tandem solar cell with a selective passivation contact structure according to claim 6, characterized in that: In step (3), when the insulating high molecular polymer is in situ polymerized, the polymer monomer and the photoinitiator are dissolved in an organic solvent to obtain a polymer monomer solution; the polymer monomer solution is spin-coated on the bottom of the pyramid structure of the hole transport layer, first at a high speed and then at a low speed, so that the solution is partially volatilized, and then photo-initiated polymerization is performed, and annealing is performed to obtain a selective passivation layer.
8. The method for preparing a perovskite / silicon tandem solar cell with a selective passivation contact structure according to claim 6, characterized in that: The polymer monomers include styrene, phenyl methacrylate or glyceryl trihydroxypropyl ether triacrylate; Preferably, the photoinitiator is benzoin ethyl ether; and the organic solvent is tetrahydrofuran. Preferably, the polymer monomer accounts for 0.10% to 5.00% of the mass of the polymer monomer solution, the photoinitiator accounts for 0.02% to 0.10% of the mass of the polymer monomer solution, and the organic solvent accounts for 94.90% to 99.88% of the mass of the polymer monomer solution.
9. The method for preparing a perovskite / silicon tandem solar cell with a selective passivation contact structure according to claim 6, characterized in that: First, spin-coat at a high speed of 3500-4500 rpm for 5-10 seconds, then spin-coat at a low speed of 1000-2000 rpm for 5-20 seconds to partially evaporate the solution, keep the spin-coating speed unchanged, irradiate with ultraviolet light for 15-20 seconds, and finally anneal at 100-110°C for 1-5 minutes.
10. The method for preparing a perovskite / silicon tandem solar cell with a selective passivation contact structure according to claim 6, characterized in that: When the polymer monomer is styrene, ultraviolet irradiation is performed for 20 to 30 seconds for prepolymerization before spin coating; when the polymer monomer is glycerol trihydroxypropyl ether triacrylate, after low-speed spin coating, heating is performed at a temperature below 150° C. for 10 to 30 seconds to promote volatilization of the polymer monomer.
Citation Information
Patent Citations
Perovskite solar cell with passivated hole transport interface and preparation method thereof
CN116096105A
Laminated solar cell and preparation method thereof
CN117255576A
Solar cell and preparation method thereof
CN118922000A
Perovskite-silicon based stacked solar cell and method for producing same
JP2024544962A